The Effectiveness of Using Type A Terminals in Public Transportation Passenger Services in Padang City - Nevia Fitri, Ardinda Melli; Jumiati, Jumiati (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study delves into the effectiveness of the Type A Anak Air Terminal in facilitating public transport passenger services within Padang. The research strives to pinpoint relevant informants by employing a qualitative approach involving descriptive methods and purposive sampling. Data was amassed through interviews, observations, and documentation, which shed light on the terminal's prowess in catering to public transport passengers in the city. The study underscores that the Type A Anak Air Terminal falls short of optimal efficiency in providing public transport passenger services. Due to ongoing efforts to develop its facilities, the terminal's core objective remains largely unrealized. Furthermore, the attainment of predefined terminal targets is yet to be fully realized; a marked deficiency in passenger contentment is noted, and a discernible imbalance between input and output exists. These findings collectively emphasize the pressing need for strategic interventions spanning facility enhancement, service refinement, and operational coordination. By addressing these facets, the terminal's effectiveness can be markedly improved, ensuring the provision of gratifying public transport services within Padang. Thus, the study's insights provide a foundation for shaping necessary enhancements to align the terminal's performance more closely with its intended purpose and the expectations of its users.